Nitrogen input decreases microbial nitrogen use efficiency in surface soils of a temperate forest in northeast China - Sun, Lifei; Qiao, Yanci; Wanek, Wolfgang; Moorhead, Daryl L.; Cui, Yongxing; Peng, Yujiao; Song, Liquan; Hu, Baoqing; Zhang, Tuo; Li, Shuailin (Geoderma, 2025)
•N addition decreases microbial NUE by decreasing phosphorus availability and soil pH.•Microbial NUE is positively related to microbial biomass formation and negatively related to soil inorganic N cycling.•Microbial NUE controls the branchpoint between soil microbial N immobilization and inorganic N cycling. Microbial nitrogen use efficiency (NUE) reflects the allocation of microbially-acquired N between growth (anabolism) and the release of inorganic N to the environment (catabolism), and is central to understanding soil N cycling. However, the effects of N addition on microbial NUE are unclear. We determined microbial NUE in surface (0–10 cm) and subsurface (10–20 cm) soils in a temperate forest by the combined substrate-independent 18O-H2O tracer technique and 15N isotope pool dilution in a multi-level N addition experiment. We found that high N treatment (75 kg N ha−1 yr−1 as urea fertilizer) significantly decreased NUE in surface soil, but not in the subsurface soil. The decrease in NUE in surface soil was related to soil acidification, likely induced by N addition, and to reduced phosphorus availability, suggesting increased phosphorus limitation to microbial metabolism with N addition. Microbial NUE was inversely related to inorganic N flux (as NH4+) in both surface and subsurface soils and positively related to microbial biomass in surface soil. Our empirical evidence confirms that microbial NUE is a sensitive proxy and controlling branchpoint between soil microbial N immobilization and inorganic N cycling, which should be explicitly included in biogeochemical models to better predict soil N dynamics.